1997
DOI: 10.1046/j.1365-2141.1997.1572983.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation during preparation of therapeutic platelets affects deterioration during storage: a comparative flow cytometric study of different production methods

Abstract: Summary. Three different separation methods, all using centrifugation, are routinely used to prepare therapeutic platelet concentrates from human donor blood. Platelet concentrates derived from platelet-rich plasma (PRP-PC), buffy coat (BC-PC) and apheresis (AP-PC) were investigated at the end of production, and over an 8 d storage period. Change in platelet surface markers were measured by flow cytometry, using fluorescein-conjugated antibodies to fibrinogen, P-selectin (CD62P), GPIIb-IIIa (CD41), GPIba (CD42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
160
6
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(190 citation statements)
references
References 31 publications
23
160
6
1
Order By: Relevance
“…Cytoplasmic condensation and budding, to yield microparticles, have been associated with apoptosis in aging platelets in stored concentrates, 18 but these platelets have also undergone a degree of activation during their preparation, which increased during storage in parallel with their decline into an apoptotic-like state. 38 However, morphologic changes similar to those observed in our study were also reported during apoptosis in platelets aged in vitro, which was also accompanied by a reduced aggregatory response. 39 Exposure of patients to ABT-263 results in thrombocytopenia during the first 4 weeks of treatment.…”
Section: Discussionsupporting
confidence: 34%
“…Cytoplasmic condensation and budding, to yield microparticles, have been associated with apoptosis in aging platelets in stored concentrates, 18 but these platelets have also undergone a degree of activation during their preparation, which increased during storage in parallel with their decline into an apoptotic-like state. 38 However, morphologic changes similar to those observed in our study were also reported during apoptosis in platelets aged in vitro, which was also accompanied by a reduced aggregatory response. 39 Exposure of patients to ABT-263 results in thrombocytopenia during the first 4 weeks of treatment.…”
Section: Discussionsupporting
confidence: 34%
“…The GPIIb/IIIa receptor is responsible for platelet binding to fibrinogen and aggregation. Several studies have shown a well preserved GPIIb/IIIa expression during storage [6,21,22] but GPIIb/IIIa have also been reported to increase [23] and the receptor can exist in an activated or non-activated form, thus further complicating interpretations. Analysis of the active conformation of GPIIb/IIIa was not assessed in our study, which would have been of interest since there are studies reporting that the GPIIb/IIIa receptor undergoes changes with storage [2,24], which might be one explanation to the increased platelet binding to fibrinogen beads observed in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Surface expression of GPIIb/IIIa, Pselectin and GPIb can be measured by flow cytometry. Increased P-selectin expression during storage has been reported by several authors [15][16][17] whereas GPIb has been shown to decrease during storage [15,17]. It is however unclear whether the level of in vitro platelet activation in stored PCs correlates with in vivo survival and haemostatic function of platelets after transfusion [18].…”
Section: Flow Cytometrymentioning
confidence: 98%